AB0578 Fatigue is Closely Associated with Quality of Life in Patient with PSS and Younger Age, the Presence of Autonomic Dysfunction and Xerostomia is the Major Determinant of Severe Fatigue. (9th June 2015) - Koh, J.H.; Lee, J.; Jung, S.-M.; Min, H.K.; Kim, J.H.; Jeon, H.; Kwok, S.-K.; Ju, J.H.; Park, S.-H.
Abstract : Background: Fatigue is a common disabling extraglandular symptoms of PSS. The prevalence of clinically significant fatigue is 57-74% in patients with PSS. In addition, chronic fatigue is associated with many rheumatic diseases and affects on quality of life. However, there were no identified predictor of clinical or laboratory variables on fatigue in patients with PSS. Objectives: The aim of this study was to investigate the relationship of fatigue severity and other clinical characteristics in primary Sjogren's syndrome (pSS) and to determine factors contributing to fatigue. Methods: We analyzed 105 participants from the Korean Initiative of primary Sjogren's Syndrome (KISS), a prospective pSS cohort. Fatigue was assessed with the fatigue domain of European League Against Rheumatism Sjogren's Syndrome Patient reported index (ESSPRI). Severe fatigue was defined as an ESSPRI fatigue ≥6. Autonomic dysfunction was assessed by heart rate variability test and defined as standard deviation of normal to normal RR interval (SDNN) <30 ms in age <50 year-old patients, SDNN <20 ms in age ≥50 year-old patients or root mean square of standard deviation <10 ms. Results: The median total ESSPRI score was 5 (IQR 4–6). Forty-two percent of patients reported their fatigue score ≥6. Younger and premenopausal patients presented more fatigue ( p =0.04 and p =0.015, respectively). Dysautonomia was more frequently observed in patients with significant fatigue [22 (50%) and 17 (28%), respectively, p =0.025]. Moderate to severe xerophthalmia was observed in 71.4% of patients (n=30) with significant fatigue, whereas ocular stain score and the presence of meibomian gland dysfunction were not different according to the fatigue severity. Higher xerostomia inventory score ( p =0.011) was observed in patients with significant fatigue. Multivariate analyses identified younger age (Odd ratio (OR) 0.947, 95% confidence interval (CI) 0.904–0.992), dysautonomia (OR 2.84, 95% CI 1.045–7.718) and xerostomia inventory (OR 2.151, 95% CI 1.181–4.247) as being associated with an increased risk of significant fatigue. ESSPRI fatigue score was correlated with EQ-5D by time trade off values and vas score ( r =-0.371 [ p <0.001] and r =-0.357 [ p <0.001], respectively). Conclusions: In patients with pSS, younger age, xerostomia and dysautonomia increase the risks for significant fatigue. References: Segal B, Thomas W, Rogers T, Leon JM, Hughes P, Patel D, et al. Prevalence, severity, and predictors of fatigue in subjects with primary Sjogren's syndrome. Arthritis and rheumatism. 2008;59(12):1780-7. Ng WF, Bowman SJ. Primary Sjogren's syndrome: too dry and too tired. Rheumatology (Oxford, England). 2010;49(5):844-53. Barendregt PJ, Visser MR, Smets EM, Tulen JH, van den Meiracker AH, Boomsma F, et al. Fatigue in primary Sjogren's syndrome. Annals of the rheumatic diseases. 1998;57(5):291-5. Acknowledgements: This study was supported by a grant from the Korean Health Technology R&D Project, Ministry of Health & Welfare, Republic of Korea (HI13C0016). Disclosure of Interest: None declared